ASSOCIATION OF SMARTPHONE USAGE AND HAND GRIP STRENGTH AMONG UNIVERSITY STUDENTS: A CORRELATION STUDY - Mirza Baig, Aftab Ahmed; Batool, Tooba; Sonia, Ayesha; Khan, Aimen; Hassan, Rabia (Annals of Allied Health Sciences, 2023)
Objective: To determine the frequency of smartphone usage and its association with hand grip strength among university students. Material & Methods: Three hundred and twenty-two university students were recruited in a cross-sectional study in duration from July to October. Informed consent was taken. Demographics were recorded. Smartphone usage was assessed through the Smartphone addiction scale –short version. Hand grip strength was evaluated with Jamar handheld dynamometer. Results: The mean age of 322 participants were 21±1.7 years with 212 (65.8%) females and 110 (24.2%) males. Result showed 87 (27.01%) frequent smartphone users out of 322 participants. However, the grip strength did not correlate smartphone usage (r = 0.06; P < 0.91). Conclusion: It concludes that the smart phone usage is less frequent among university students and hand grip strength does not associate with smartphone usage.